Prospective study on embolization of intracranial aneurysms with the pipeline device (PREMIER study): 3-year results with the application of a flow diverter specific occlusion classification. (15th March 2022) - Hanel, Ricardo A; Cortez, Gustavo M; Lopes, Demetrius Klee; Nelson, Peter Kim; Siddiqui, Adnan H; Jabbour, Pascal; Mendes Pereira, Vitor; István, Istvan Szikora; Zaidat, Osama O; Bettegowda, Chetan; Colby, Geoffrey P; Mokin, Maxim; et al.
Abstract : Background: The pipeline embolization device (PED; Medtronic) has presented as a safe and efficacious treatment for small- and medium-sized intracranial aneurysms. Independently adjudicated long-term results of the device in treating these lesions are still indeterminate. We present 3-year results, with additional application of a flow diverter specific occlusion scale. Methods: PREMIER (prospective study on embolization of intracranial aneurysms with pipeline embolization device) is a prospective, single-arm trial. Inclusion criteria were patients with unruptured wide-necked intracranial aneurysms ≤12 mm. Primary effectiveness (complete aneurysm occlusion) and safety (major neurologic event) endpoints were independently monitored and adjudicated. Results: As per the protocol, of 141 patients treated with a PED, 25 (17.7%) required angiographic follow-up after the first year due to incomplete aneurysm occlusion. According to the Core Radiology Laboratory review, three (12%) of these patients progressed to complete occlusion, with an overall rate of complete aneurysm occlusion at 3 years of 83.3% (115/138). Further angiographic evaluation using the modified Cekirge–Saatci classification demonstrated that complete occlusion, neck residual, or aneurysm size reduction occurred in 97.1%. The overall combined safety endpoint at 3 years was 2.8% (4/141), with only one non-debilitating major event occurring after the first year. There was one case of aneurysm recurrence but no cases of delayed rupture in this series. Conclusions: The PED device presents as a safe and effective modality in treating small- and medium-sized intracranial aneurysms. The application of a flow diverter specific occlusion classification attested the long-term durability with higher rate of successful aneurysm occlusion and no documented aneurysm rupture. Trial registration: NCT02186561 .